Development Of Artificial Intelligence, Social Applications And The Strategic Role Of The Teacher In Education: Uzbekistan's Experience, Risks And Management Models (Eurasian Research Bulletin, 2026)
This article provides a comprehensive analysis of the scientific debates surrounding the rapid development of artificial intelligence, its penetration into various spheres of society, the stages of the formation of artificial intelligence policy in Uzbekistan, institutional and infrastructural changes, and the possibility of artificial intelligence systems moving beyond human control in the long term. The main idea of the study is that the true value of artificial intelligence is not in its technical power, but in how it is managed in interaction with society, the state, and the education system. In this context, the article discusses the practical results of using artificial intelligence in healthcare, agriculture, public administration, finance, industry, and education, as well as negative consequences such as misinformation, algorithmic bias, shifts in the labor market, threats to privacy, cybersecurity, pedagogical dependence, and the weakening of human agency. In the case of Uzbekistan, the “Strategy for the Development of Artificial Intelligence Technologies until 2030” adopted in 2024, priority projects for 2025–2026, supercomputer and data infrastructure, the new legal environment formed in 2026, and the activity of the private sector are revealed based on modern sources. In the education section, the teacher is interpreted not as a replaceable subject of artificial intelligence, but as a strategic figure who sorts content, sets moral criteria, provides metacognitive guidance, and organizes real learning. The research was conducted using documentaryanalytical, comparative, and scenario-based methods. The results show that the benefits of artificial intelligence do not arise automatically, but only when combined with humancentered management, strong pedagogical leadership, responsible regulation, and local scientific potential.